Application Optimazion Of Fidelity Watermarking Digital Imegery Discrete Fourier Transform Method And Rivest Shamir Adleman Algorithm - Wulan, Nur; Harahap, Herlina; Sari Siregar, Yunita (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
As the field of information and communication technology continues to evolve, the potential for digital crimes increases significantly. Information technology plays a key role in facilitating various human activities in the fields of communication and data exchange. The use of digital data, such as documents, photos, videos, and audio, still creates many challenges in proving ownership.. The proliferation of social media platforms like Facebook, Instagram, and TikTok has made it easier for individuals to duplicate, damage, or even steal content, often for malicious purposes related to copyright infringement.To secure digital image data, the technique of fidelity watermarking using Discrete Fourier Transform (DFT) and cryptographic authentication with the Rivest-Shamir-Adleman (RSA) algorithm can be utilized. Watermarking is a technique that embeds information into an image, serving to provide identification marks and secure copyright information. This process does not damage the original image quality. DFT is a watermarking technique that has the capability to convert the image back to the spatial domain after embedding the watermark. On the other hand, RSA is a cryptographic technique that enables data encryption using a public key and decryption with a private key. In the context of image watermarking, RSA is used to secure the watermark information embedded within the image. Watermark information that is encrypted using the public key can only be accessed or decrypted by the party possessing the private key. This enhances the security of the watermark and ensures that the information embedded within the image remains safe, even if the image is shared.